PARADOKS PROMOSI JABATAN APARATUR SIPIL NEGARA DALAM MERIT SYSTEM: STUDI KASUS: PROMOSI JABATAN DI LINGKUNGAN PEMPROV KALIMANTAN TENGAH - Luthfie, Muhammad; Sastrawan, Berry; Saprudin, Saprudin; Hamka, Hamka (Administratie: Jurnal Administrasi Publik, 2023)
The research focused on the process of promotion to high pratama position or echelon 2 in Central Kalimantan Province which was allegedly colored by deviations from the mandate of the ASN Law or paradoxes. The aim of the research is to analyze political intervention in the promotion of positions within the Central Kalimantan Provincial Government and to analyze the paradox of promotion to ASN positions in the Merit System within the Central Kalimantan Provincial Government. The research method uses a qualitative approach with case studies combined with grounded theory. The results of the study show that political intervention occurred in the implementation of promotions to high pratama or echelon 2 positions in the Central Kalimantan Provincial Government and the paradox of promotion can be seen from the absence of a relationship between the results of promotion and the merit system.